Chemical Composition and Biological Activities of St John’s Wort (Hypericum perforatum L.) Essential Oil from Bulgaria - Yulian Tumbarski; Ivan Ivanov; Mina Todorova; Anelia Gerasimova; Ivayla Dincheva; Lubomir Makedonski; Krastena Nikolova (Applied Sciences)
Since ancient times, essential oils obtained from various aromatic plants have been utilized as bioactive ingredients in medicines, foods and cosmetics. The present study aimed to investigate the chemical composition and biological activities of St John’s Wort (Hypericum perforatum L.) essential oil (SJW EO) from Bulgaria, which is known to possess various biological properties. Gas chromatography and mass spectrometry (GC–MS) analysis, determination of antioxidant activity (by the ABTS method), an antimicrobial activity test and an in vitro anti-inflammatory activity test were performed. The main classes of compounds identified by GC–MS analysis were monoterpenes (43.55%), followed by sesquiterpenes (36.81%) and alkanes (16.92%). The predominant chemical components of SJW EO were α-pinene (27.52%), followed by β-pinene (10.08%), β-caryophyllene (6.77%), germacrene D (6.37%) and caryophyllene oxide (4.48%). The highest antibacterial activity was observed against the Gram-negative bacteria Klebsiella pneumoniae ATCC 13883 (inhibition zone of 12.0 mm) and Pseudomonas aeruginosa ATCC 9027 (inhibition zone of 11.0 mm). SJW EO exhibited significant in vitro anti-inflammatory activity, as the results demonstrated that its anti-inflammatory effect was stronger than those of the conventional anti-inflammatory drugs Prednisolon Cortico and acetylsalicylic acid (Aspirin), which were used as controls (all in concentration of 1 mg/mL). The obtained results demonstrated that Bulgarian SJW EO can be used as an active ingredient in the composition of new products for the pharmaceutical and cosmetic industries.